The Role of Kinship and the Effectiveness of Traditional Customary Law on Inheritance System in Berbah, Sleman Regency (Medico Legal Update, 2021)
Indigenous peoples in Indonesia have a diverse family system, this leads to diversity in the devolutionsystem. This form of parental kinship applies to the people of Berbah Sub-District of Sleman Regency. Andwhoath is in the heavens and the earth, and who is in the heavens and the earth, and who is in the heavensand the earth, and who is in the heavens and the earth, and whoth in the heavens and the earth, and currently,the people in Berbah Sub-District of Sleman Regency are predominantly Muslim, which could potentiallyinfluence the pattern of setting inheritance distribution in Islamic Law. There is still a strong principle oftogetherness, the principle of deliberation, and the principle of benefit in the order of life of the people ofBerbah District of Sleman Regency. Most importantly, they can accept the results of deliberation whileupholding the principle of harmony